Pendekatan Humanistik Dalam Pembelajaran Bahasa Arab Perspektif K.H. Ahmad Dahlan - Hijriyah, Athiyah Laila; Putri, Annindita Hartono; Sovinaz, Sovinaz; Isnaini, Rohmatun Lukluk (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
This research aims to examine the humanistic approach to learning Arabic, according to K.H. Ahmad Dahlan. The method used is descriptive-qualitative through library research with the primary data source "Advanced Educational Paradigm: Theory and Praxis of KH Ahmad Dahlan's Religious Progressive Education," where in the book KH Ahmad Dahlan examines teaching methods and approaches to both Islamic religion and knowledge in general and Arabic, and secondary data sources originating from various books and scientific works that study this character. Data was collected using documentation techniques and analyzed using content analysis. The research results show that the humanistic approach to learning Arabic, according to K.H. Ahmad Dahlan, emphasizes a personal, interactive, and contextual approach. This approach does not only focus on language mastery but also on developing students' potential as a whole, including spiritual, moral, and social aspects. There are three principles of learning Arabic: explaining the objectives of learning Arabic to students and providing practice in mastering Arabic language skills; playing language roles with students according to the current context; and providing examples of using Arabic to students. Furthermore, humanistic implementation in Arabic language learning involves using relevant learning methods according to students' needs, such as thariqah mubasyarah, student exchange programs, language immersion classes, interaction between students and native speakers, creating bi'ah lughawiyyah, and instilling an understanding of the social context. and Arab culture.